Managing BPO and IT outsourcing - Willcocks, Leslie (Henry Stewart Talks, 2011)
The IT outsourcing market, Asking the right questions, The outsourcing learning curve, Main risks in IT outsourcing, The winner's curse, Strategic sourcing, Nine core back-office capabilities, Underlying types of relationship, Supplier capabilities, Contract management, Anatomy of an outsourcing deal, Outsourcing contracts, Lifecycle cost escalation, Contract scorecard dashboard, Customer service, Outsourcing principles, References
Archived at 2022/04/26